An efficient pixel-level chaotic image encryption algorithm - Ye, Guodong; Pan, Chen; Huang, Xiaoling; Mei, Qixiang (Nonlinear dynamics, 2018)
In this paper, a new and efficient pixel-level image encryption algorithm is presented. In contrast to the traditional permutation–diffusion architecture, the proposed method enhances the connection between position shuffling for pixels and value changing for grayness. As a result, the separate attack becomes more difficult when attacking our structure of permutation–rewriting–diffusion (PRD). Before the diffusion operation, a rewriting function is applied to the permuted image in a simple way, which can be seen as a remedy for permutation’s inability to change the frequency of pixels. Moreover, the keystream is designed dependent upon the plain-image. Therefore, the proposed method can disturb the chosen plain-image and known plain-image attacks. Experimental results together with security analysis also show good efficiency of the PRD mechanism. Compared to some bit-level-based image encryption algorithms, our method shows increased faster speed and satisfies the performance requirements of real-time communication.